2008
DOI: 10.1007/s00420-008-0326-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between five self-administered instruments predicting sick leaves in a 4-year follow-up

Abstract: Objectives This study aimed to explore and compare the ability of five instruments for self-rating to predict future sick leave rates. MethodsIn three Swedish municipalities 2 252 employees completed a baseline questionnaire and were followed up for 4 years. Five health-oriented instruments for self-rating were used as potential predictors of the two outcome measures no sick leave at all, and one or more spells of long-term sick leave ≥ 28days. Positive and negative predictive values as well as Cox proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
4
23
2
2
Order By: Relevance
“…Lindberg et al (18) investigated the predictive value of the WAI for LTSA episodes ≥28 days in a population-based sample (N=2252) from three Swedish municipalities. The authors found that workers with poor-to-moderate WAI scores had a 1.6 (women) to 2.1 (men) times higher risk of LTSA as compared to workers with good to excellent WAI scores.…”
mentioning
confidence: 99%
“…Lindberg et al (18) investigated the predictive value of the WAI for LTSA episodes ≥28 days in a population-based sample (N=2252) from three Swedish municipalities. The authors found that workers with poor-to-moderate WAI scores had a 1.6 (women) to 2.1 (men) times higher risk of LTSA as compared to workers with good to excellent WAI scores.…”
mentioning
confidence: 99%
“…Kujala et al [38] showed that poor work ability, defined as a low score on the WAI, was associated with sickness absence for men and women. The WAI is also predictive of future sick leave, particularly long-term sick leave and receiving a disability pension [67,68] This study has some limitations that must be considered when interpreting the results and does not guarantee generalisability for all employees with MSD and/or MD. We used a convenience sample, which mainly consisted of female employees working in the public sector and with long-standing symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…The WAI is a broad tool that captures several dimensions of relevance for work ability and sick leave. The WAI is considered a feasible screening tool [68] and can be used as a first step in assessing work ability to obtain a general picture of how well an employee with MSD and/or MD is able to perform their work. The well as physical and mental conditions [41].…”
Section: Discussionmentioning
confidence: 99%
“…The current study assessed self -rated health (SRH), which has been shown to predict sickness absence, ill health and mortality (Lindberg et al, 2009;SinghManoux et al, 2007). DGB-Index scores were higher amongst those who reported that their health was good than those who considered their health to be fair or poor (Table 5) and amongst those who believed that their work was good for their health.…”
Section: The Dgb-index and Healthmentioning
confidence: 99%